Bioremediation and microbiome-generating electricity in butter catfish (Ompok bimaculatus) aquaculture wastewater treatment via water fern (Azolla microphylla) - Thipraksa, Junjira; Yooyen, Thanapon; Chainapong, Thaweedet; Michu, Panisa; Kongthong, Alisa; Chaijak, Pimprapa (Journal of Degraded and Mining Lands Management, 2024)
The increasing volume of wastewater from fish farming poses a serious environmental threat. This study investigated a novel treatment method for butter catfish (Ompok bimaculatus) wastewater using a constructed wetland-microbial fuel cell (CW-MFC) integrated with the water fern Azolla microphylla. The system was effectiveness in removing pollutants like electrical conductivity (EC), total dissolved solids (TDS), ammonium, nitrate, nitrite, and phosphate was evaluated. Additionally, the electricity generation capabilities were measured. The CW-MFC system achieved significant removal rates: 67.65% for EC, 61.67% for TDS, 100% for ammonium, 75.00% for nitrate, 81.25% for nitrite, and 70.00% for phosphate. Furthermore, the system generated a maximum open-circuit voltage (OCV) of 690±90 mV, a current density (CD) of 7.29±0.43 mA/m³and a power density (PD) of 0.37±0.04 mW/m³. Analysis of the microbial community revealed a diverse root consortium dominated by bacterial genera including Phreatobacter, Emticicia and Rhodobacter, along with fungal genera such as Strelitziana, Ramularia, Cladosporium,Trichomerium, Cercospora, Erythrobasidium and Fusarium. These findings suggest that CW-MFC systems integrated with A. microphylla offer a promising approach for sustainable and efficient treatment of wastewater from catfish farming while simultaneously generating bioelectricity.